2016
DOI: 10.1016/j.ejca.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

European Research on Electrochemotherapy in Head and Neck Cancer (EURECA) project: Results of the treatment of skin cancer

Abstract: Electrochemotherapy is an effective and safe method for local treatment of cutaneous and subcutaneous tumours, where electric pulses cause increased permeability of cell membranes in the tumour mass, enabling dramatically enhanced effectiveness of bleomycin and other hydrophilic drugs. Here, we report results of a European multi-institutional prospective study of the effectiveness of electrochemotherapy in the treatment of skin cancer of the head and neck (HN) area, where standard treatments had either failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
150
2
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(184 citation statements)
references
References 26 publications
9
150
2
16
Order By: Relevance
“…It is remarkable that no comparative trials have been carried out so far and no cost-analyses are available. The bulk of the literature consists of small observational series, often including heterogeneous skin cancers [10, 12, 1418, 24]. In an early trial, Glass et al [16] reported a 98% response rate after one or more ECT cycles with intralesional bleomycin and no recurrences detected after 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is remarkable that no comparative trials have been carried out so far and no cost-analyses are available. The bulk of the literature consists of small observational series, often including heterogeneous skin cancers [10, 12, 1418, 24]. In an early trial, Glass et al [16] reported a 98% response rate after one or more ECT cycles with intralesional bleomycin and no recurrences detected after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis assessing 47 prospective studies on patients with cutaneous metastases—mainly from melanoma and breast cancer—treated by skin-directed therapies (including ECT, radiation, photodynamic, intralesional and topical therapies) showed sustained response rates across treatments with G ≥ 3 dermatological toxicity in less than 6% of patients [26]. More recently, a European and an Italian multicenter studies (both adopting the ESOPE protocol), have reported CR rates of 91 and 66.7%, respectively, in BCC patients, although with a short follow-up (6 and 13.9 months, respectively) [10, 11]. In 2016, Rotunno et al reported a 75% CR rate in patients with head and neck BCC treated by ECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 2 months from ECT SCC group showed the higher percentage of OR (79%) with 55% of CR and 24% of PR. Interestingly, for recurrent tumour nodules, previous surgery least affected the outcome compared to (chemo) radiotherapy or multiple treatments [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated the safety and efficacy of ECT in the tumor control of a wide range of primary and metastatic malignancies 68,13. In particular, ECT has been shown to be a safe and effective treatment option in a palliative setting for melanoma cutaneous and subcutaneous metastases 1416.…”
Section: Discussionmentioning
confidence: 99%